2012
DOI: 10.1111/j.1469-0691.2012.03928.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of New Delhi metallo-β-lactamase-1-producing Acinetobacter baumannii in Europe

Abstract: Multidrug-resistant and New Delhi metallo-β-lactamase 1 (NDM-1) -producing Acinetobacter baumannii are increasingly reported. A collection of five NDM-1-positive A. baumannii isolates recovered in four European countries were analysed. Genotyping was performed by pulsed-field gel electrophoresis, multiplex PCR sequence typing, Diversilab and multilocus sequence typing. Three distinct sequence types were identified. All isolates harboured a chromosomally located bla(NDM-1) gene within a Tn125-like transposon. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 26 publications
8
112
2
3
Order By: Relevance
“…Genotypic comparison by pulsed-field gel electrophoresis using restriction enzyme SmaI revealed an indistinguishable profile (data not shown). Diversilab (bioMérieux, France) analysis and multilocus sequence typing (MLST) typing confirmed that these isolates were clonally related and belonged to the same sequence type, ST85 (Figure 2) [8]. The genetic environment of blaNDM-1 was investigated as previously described [8] and showed that it was located in the composite transposon Tn125 made of two copies of insertion sequence (IS) ISAba125.…”
Section: Laboratory Analysismentioning
confidence: 55%
See 3 more Smart Citations
“…Genotypic comparison by pulsed-field gel electrophoresis using restriction enzyme SmaI revealed an indistinguishable profile (data not shown). Diversilab (bioMérieux, France) analysis and multilocus sequence typing (MLST) typing confirmed that these isolates were clonally related and belonged to the same sequence type, ST85 (Figure 2) [8]. The genetic environment of blaNDM-1 was investigated as previously described [8] and showed that it was located in the composite transposon Tn125 made of two copies of insertion sequence (IS) ISAba125.…”
Section: Laboratory Analysismentioning
confidence: 55%
“…Since 2010, NDM-producing MDR-AB has been identified in various parts of the world, in particular in North Africa and the Middle East [8,[13][14][15][16][17]. A series of imported cases have been identified recently in Europe, such as in the Czech Republic, Germany, Slovenia, Switzerland and Belgium [8,13,14,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbapenemases in Acinetobacter spp. belong to Ambler class A (KPC and some GES variants) (Bonnin et al, 2013b;Robledo et al, 2010), class B (VIM, IMP, SIM, NDM) (Bonnin et al, 2012;Poirel and Nordmann, 2006), and mostly class D (oxacillinases) (Bonnin et al, 2013a). Five main groups of oxacillinases with carbapenemase activity have been identified in A. baumannii, i.e., the intrinsic chromosomal OXA-51-like and the acquired chromosomally and plasmid-encoded OXA-23-like, OXA-40-like, OXA-58-like, and OXA-143-like enzymes (Bonnin et al, 2013a;Higgins et al, 2009;Poirel and Nordmann, 2006).…”
mentioning
confidence: 99%